The educational investment as a paradigm of the politics of the Welfare State retrenchment: an analysis of the Spanish regional context after the 2008 systemic crisis - Sánchez Villar, Juan Mª (Revista Complutense de Educación, 2018)
In Spain, the 2008 systemic crisis and its prolonged duration have resulted in additional challenges for the maintenance of the Welfare State and, especially, for the education, the most retrenched fundamental public service during these years. This research deepens in the evolution of the educational investment in the different regions of Spain throughout this critical period 2008-2013 and tries to gain insight into the role the public administration has played when budgeting this line, too. To do so, this paper has composed two separate groups of Spanish regions according to the economic impact of the 2008 crisis, and has carried out a longitudinal and comparative analysis basing on several indicators. Results show how political will has become the major element to establish the general guidelines of the educational investment and, additionally, that the disparities observed between different political approaches are minimum. The implications of these results do usher in a wider interpretation on the importance and need to redefine education as the generating vector of social capital in Spain, as well as to a more profound political discussion on financial resourcing in the context of the current Welfare State.